Bacteria isolated from roots and rhizosphere of Vitis vinifera retard water losses, induce abscisic acid accumulation and synthesis of defense‐related terpenes in in vitro cultured grapevine. Issue 4 (4th November 2013) - Salomon, María Victoria; Bottini, Rubén; de Souza Filho, Gonçalo Apolinário; Cohen, Ana Carmen; Moreno, Daniela; Gil, Mariana; Piccoli, Patricia
Abstract Eleven bacterial strains were isolated at different soil depths from roots and rhizosphere of grapevines from a commercial vineyard. By 16S rRNA gene sequencing 10 different genera and 8 possible at species level were identified. From them, Bacillus licheniformis Rt4M10 and Pseudomonas fluorescens Rt6M10 were selected according to their characteristics as plant growth promoting rhizobacteria (PGPR). Both produced abscisic acid (ABA), indole‐3‐acetic acid (IAA) and the gibberellins A1 and A3 in chemically‐defined medium. They also colonized roots of in vitro grown Vitis vinifera cv. Malbec plants. As result of bacterization ABA levels in 45 days‐old in vitro plants were increased 76‐fold by B. licheniformis and 40‐fold by P. fluorescens as compared to controls. Both bacteria diminished plant water loss rate in correlation with increments of ABA. Twenty and 30 days post bacterization the plants incremented terpenes. The monoterpenes α‐pinene, terpinolene, 4‐carene, limonene, eucalyptol and lilac aldehyde A, and the sesquiterpenes α‐bergamotene, α‐farnesene, nerolidol and farnesol were assessed by gas chromatography‐electron impact mass spectrometry analysis. α‐Pinene and nerolidol were the most abundant (µg per g of tissue in plants bacterized with P. fluorescens). Only α‐pinene, eucalyptol and farnesol were identified at low concentration in non‐bacterized plants treated with ABA, while no terpenes were detected in controls. The results obtained along with others from literature suggest that B. licheniformis and P. fluorescens act as stress alleviators by inducing ABA synthesis so diminishing water losses. These bacteria also elicit synthesis of compounds of plant defense via an ABA independent mechanism.